Impact and implications of youth involvement in urban gangs: a case study from Nasarawa, Kano State, Nigeria - Amali, Sadiq Ewaoda (Acta criminologica, 2017)
This article explores some of the causes of the growth of urban gangs in the Nasarawa local area district of Kano city in Kano State, Nigeria, with an emphasis on the implications and impact of youth involvement in the so-called Yandaba Urban Gangs. In Nasarawa the law enforcement and other security agencies have lacked the capacity to fully implement protection of citizens and law and order. This shortcoming is amply demonstrated through incompetence, a shortage of logistical resources - i.e. poorly equipped - and the overrating of their own abilities to combat the activities of the urban gangs in the Yandaba Ward of Nasarawa. The main aim of this research was to examine the causes, impact and implications of urban gangs for security and the factors that influence an individual to engage in criminal activities. A quantitative research design was applied to examine the causes and implications of urban gang formation. The population of the study involved members of the Yandaba urban youth gangs, residents and some law enforcement officers such as police officers of various divisions of the Nasarawa Local Government. The target population was drawn from eight (of ten) wards in the Nasarawa Local Government District, namely: Giginyu, Kawo, Badawa, Sauna, Brigade, Tudun Wada, Yankaba and Hotoro. The total sample size was 1 280 with a total of 160 respondents being purposively selected from each of the selected ward areas. The results of the analysis revealed that the inability of law enforcement agencies to control and prevent the rise in levels of crime in these ward neighbourhoods contributed substantially to the proliferation of urban gangs in the study area. Based on the results, the study concluded that law enforcement agencies in the region lack the capacity to curtail the growth and proliferation of youth gangs in the area. Accordingly, the study recommended the enhancement of the capacity of the law enforcement agencies so that they can more effectively curtail the proliferation of youth gang formation in the region.